Formulation design and optimization of orodispersible tablets of etoricoxib by response surface methodology - Shahi, S R; Agrawal, G R; Shinde, N V; Shaikh, S A; Shaikh, S S; Padalkar, A N; Somani, V G (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of the present investigation was to design a formulation of orodispersible tablets of Etoricoxib by adopting a systematic approach of 32 factorial design and to evaluate various quality control parameters. Etoricoxib is a novel, selective second-generation cyclooxygenase-2 inhibitor administered orally as an analgesic and antiinflammatory drug that is used for the treatment of osteoarthritis, rheumatoid arthritis and gouty arthritis. The poor aqueous solubility of the drug leads to variable dissolution rates. In the present investigation, an attempt has been made to prepare orodispersible tablets of Etoricoxib using three different directly compressible fillers to improve mouthfeel with an enhanced dissolution rate. In the study, a 32 full factorial design was adopted to investigate the joint influence of two formulation variables: amount of mannitol and crospovidone and the evaluation thereof. Response surface plots were also presented to represent graphically the effect of the independent variables on the disintegration time and drug percent dissolved in 60 s. The statistical model is mathematically valid as the experimental (actual) values and predicted values suggested by the full model were relatively close to each other. This systematic formulation approach will help in understanding the effect of formulation variables and permits the arbitrary selection of a batch of tablets with improved dissolution profile after oral administration of the selective COX-2 inhibitor.